MENGAJARKAN IBU HAMIL MELANTUNKAN ASMAUL HUSNA DIKELAS IBU HAMIL POLINDES BERBELUK - Iin Setiawati; Selvia Nurul Qomari (STIKES NGUDIA HUSADA MADURA, 2023)
Anxiety and depression during pregnancy are major problems that occur in society because of their high prevalence. This anxiety occurs from the first trimester until delivery, but several studies have stated that the level of depression or anxiety during the early trimester is the same as normal anxiety, while the level of depression or anxiety during the second and third trimesters is almost double that of the first trimester. The purpose of community service is to reduce the anxiety level of pregnant women by chanting Asmaul Husna. The method used for this community service is to first ask permission from the Berbeluk polindes midwife to take part in the holding of pregnant women classes. The implementation of community service at the Polindes Berluk runs smoothly. Pregnant women feel helped by the community service that we do. It can be seen from the results of the questionnaire that showed a decrease in the value of anxiety in pregnant women before and after chanting Asmaul Husna. For further development, it can be accompanied by music so that reading Asmaul Husna becomes more interesting